Considerações sobre a noção de coragem nas Epistulae Morales ad Lucilium de sêneca - Mariana Monteiro Conde (2014)
Seneca shows us, in his Epistulae Morales ad Lucilium, a moral philosophy that is sustained and developed, often, through various metaphors, analogies and quotes related to military life. Considering these characteristics of his philosophy like symptoms of the conception of his ethical ideal, which is very similar to the virtue conceived as a confrontation of the adversities of life; our objective in this paper is to analyze the concept of courage (fortitudo) in some epistles and selected excerpts of the reported work, as well as its possible connection with the concept of happy life (beata vita). To this end, we seek to handle the issue in question through the analysis and discussion of psychological, anthropological and ethical aspects of Stoic doctrine, as expressed in the imperial period. All these tasks are intended to explain how important the process of strengthening of self is through the construction of the ethical individual to Seneca.